Contextual moral dilemma-based problem-based learning to improve student activeness and learning outcomes in elementary Pancasila education (IAIN Kendari, 2026)
Pancasila Education in elementary schools requires learning models that enable students to connect civic values with real-life moral issues. This study aimed to describe the implementation of Problem-Based Learning based on contextual moral dilemmas, analyse the improvement in student activeness, and evaluate learning outcomes among Grade V students. The study employed classroom action research conducted in two cycles involving 24 students at SD Negeri 2 Banyumudal. Data were collected through observation sheets, written tests, field notes, and informal interviews, and were analysed descriptively across the pre-cycle, Cycle I, and Cycle II stages. The findings showed consistent improvement in both learning process and achievement. Student activeness increased from 47.9% in the pre-cycle stage to 66.7% in Cycle I and 87.5% in Cycle II. Mastery learning also rose from 41.7% to 62.5% and finally 87.5%. The use of contextual moral dilemmas, group investigation, presentation, reflection, and scaffolding encouraged students to participate more actively and understand Pancasila values more meaningfully. These findings suggest that contextual moral dilemma-based PBL can support more participatory and reflective Pancasila Education in elementary classrooms. Keywords: classroom action research; contextual moral dilemma; learning outcomes; Pancasila Education; problem-based learning; student activeness